Foundation XML and E4X for Flash and Flex - Jacobs, Sas (Friends of Ed, 2009)
"XML is the lingua franca of the Web. All designers and developers working in a web environment need a sound understanding of XML and its role in application development." "In this book, Sas Jacobs gives you an introduction to SML and E4X. She explores the new XML and XMLList classes and explains E4X expressions, providing examples for both Flash and Flex. In addition to explaining how to incorporate XML documents in SWF applications. Sas Jacobs shows you approaches specific to Flash and Flex and explores real-world usage. The book finishes with two case studies. In the first, you will learn how to consume and display information and images from Flickr using Flash. In the second, you will work with Adobe Kuler in Flex."--Jacket